Proceedings of the 2005 Symposium on Interactive 3D Graphics and Games 2005
DOI: 10.1145/1053427.1053443
|View full text |Cite
|
Sign up to set email alerts
|

Geopostors

Abstract: The simulation of large crowds of humans is important in many fields of computer graphics, including real-time applications such as games, as they can breathe life into otherwise static scenes and enhance believability. We present a novel hybrid rendering system for crowds that solves the classic problem of degraded quality of image-based representations at close distances by building an impostor rendering system on top of a full, geometry-based, human animation system. This enables almost imperceptible switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(9 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The body‐parts identification and encoding process was performed using Autodesk 3DS Max. This technique has been widely accepted and employed for giving variety to crowds with few unique body meshes ([DHOO05], [MLD*08]). Similarly, De Heras et al [dHCSMT05] make a few grayscale base textures to create a variety of avatars differentiated by the colour of their clothing and accessories; this approach is based on alpha map channels encoding and deals with situations where triangles in the mesh template correspond to more than one region with different colours.…”
Section: Visualisationmentioning
confidence: 99%
“…The body‐parts identification and encoding process was performed using Autodesk 3DS Max. This technique has been widely accepted and employed for giving variety to crowds with few unique body meshes ([DHOO05], [MLD*08]). Similarly, De Heras et al [dHCSMT05] make a few grayscale base textures to create a variety of avatars differentiated by the colour of their clothing and accessories; this approach is based on alpha map channels encoding and deals with situations where triangles in the mesh template correspond to more than one region with different colours.…”
Section: Visualisationmentioning
confidence: 99%
“…Impostors are 2D animated images, mapped onto a quad formed by 2 triangles. One pioneer work in this domain was achieved by Dobbyn et al [2]: they used pre-computed rigid meshes in front of the camera, and switched seamlessly to impostors for more distant characters. Later, Millan and Rudomin [3] presented a solution combining impostors and instanced geometries, maximizing the use of the GPU.…”
Section: Real-time Crowd Simulationmentioning
confidence: 99%
“…More recently, Kavan et al [4], presented a virtual human new level of detail, called polypostor : they are composed of a small set of 2D polygons, and animated by displacing their vertices. To avoid crowds of cloned entities, much work has been achieved on color variety, or how to modulate the colors of body parts for each instance of a same characters [5,2,6]. A recent study [7] has demonstrated that variety at the color level has much more impact on the user than varying the animations solely.…”
Section: Real-time Crowd Simulationmentioning
confidence: 99%
“…Crowd Visualization is a specific problem with various solutions [1], [2], [3]. Briefly, these solutions rely on two major concepts.…”
Section: Related Workmentioning
confidence: 99%